Landau theory for magnetic and structural transitions in CeCo0.85Fe0.15Si. (26th June 2018) - Oropesa, William Gabriel Carreras; Correa, Víctor F; Sereni, Julián G; García, Daniel J; Cornaglia, Pablo S
Abstract: We present a phenomenological analysis of the magnetoelastic properties of CeCo0.85 Fe0.15 Si at temperatures close to the Néel transition temperature T N . Using a Landau functional we provide a qualitative description of the thermal expansion, magnetostriction, magnetization and specific heat data. We show that the available experimental results (Correa et al 2016 J. Phys.: Condens. Matter 28 346003) are consistent with the presence of a structural transition at and a strong magnetoelastic coupling. The magnetoelastic coupling presents a Janus-faced effect: while the structural transition is shifted to higher temperatures as the magnetic field is increased, the resulting striction at low temperatures decreases. The strong magnetoelastic coupling and the proximity of the structural transition to the onset temperature for magnetic fluctuations, suggest that the transition could be an analogue of the tetragonal to orthorhombic observed in Fe-based pcnictides.